A comparative study of intelligent reflecting surface and relay in satellite communication - Khan, Mohammed Rabbul Hossain; Ziad, Muhammad Omar; Chowa, Sumaiya Mazed; Mehedi, Md. Mohiuddin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.